Penatalaksanaan Bantuan Hidup Dasar (BHD) Pada Masyarakat Awam (Santri Ponpes Yambuul Hikmah) Di Andong Boyolali - Akhmad Rifai; Muh Ilyas ((JKG) Jurnal Keperawatan Global, 2018)
Abstract Background: Heart disease is the number one cause of death, accounting for 39% of all deaths in the world. Basic Life Assistance (BLS) should be given to victims who suffer from stopping breathing, cardiac arrest, and bleeding. The purpose of this study was to determine the ability of Basic Life Support Skills (BLS) santri Ponpes Yambuul Hikmah in Andong Boyolali. Methods: This research is an experimental research with approach of Pre-Tes-Post Test Group design. through testing of research hypotheses. The population of this study is the people of cloud (santri Ponpes Yambul Hikmah)amounted to 50 respondents. Statistical test in pairs of groups using nonparametric Wilcoxon test. Result: Based on Wilcoxon test results it can be concluded that 50 respondents who Basic Life support Assistance (BLS) training can be drawn conclusion that the majority of santri have good knowledge in terms of emergency handling capability especially Basic Life Support with p value 0,001 which means there is a difference that takes place between before and after training. Conclusion: put forward in this research is education and training BLS of santri continue to be held at otherboarding school to improve the ability of BLS.